Empowering Coastal Communities through Oyster Shell Waste Management and Circular Economy Practices in Gisik Cemandi - Tamyiz, Muchammad; Purnama, Agus Rachmad; Reza Prasetyo, Faris (LPPM Universitas Jambi, 2024)
Managing oyster shell waste in coastal regions remains a significant issue, requiring solutions that add economic value while ensuring environmental sustainability. This community service program supported residents of Gisik Cemandi Village in converting oyster shell waste into livestock feed, aligning with circular economy principles. Activities included observations, interviews, educational sessions, discussions, training, and practical application. The initiative showed promising results: 90% of participants recognized the benefits of waste processing, and 70% showed enthusiasm for future training. It effectively increased community knowledge and skills in producing livestock feed from shell waste. From a scientific perspective, it highlights the application of circular economy and social innovation using local resources. Socially, it empowered the community—particularly women in the shellfish sector—and promoted local food security. Challenges such as limited processing tools will be addressed through proposed equipment support, the formation of small cooperatives, and ongoing community-based training. These efforts aim to ensure long-term sustainability and establish Gisik Cemandi as a model for community-driven waste management that aligns with sustainable development goals.